Analisis Morfologis daLam Novel Sarinah: Kewadjiban Wanita dalam Perdjoangan Republik Indonesia Karya Ir. Sukarno Beserta Implementasinya di SMA - Islami, Esti; , Drs. Yakub Nasucha, M.Hum (2017)
The purpose of this research is to describe the morphological process in a Sarinah: Kewadjiban Wanita dalam Perdjoangan Republik Indonesia novel by Ir. Sukarno and implementing the morphological processes in the Sarinah: Kewadjiban Wanita dalam Perdjoangan Republik Indonesia novel by Ir.Sukarno toward Indonesian lessons in high school (SMA). The sources of data in this research is Sarinah: Kewadjiban Wanita dalam Perdjoangan Republik Indonesia novel by Ir. Sukarno in 1963. In the collecting data the researcher use see and record technique. The theory that used is Chaer's theory about the morphological processes. Type of this research is descriptive qualitative. The researcher analyze using the interactive analysis techniques. This research shows that morphological processes in the Sarinah: Kewadjiban Wanita dalam Perdjoangan Republik Indonesia novel by Ir. Sukarno classified in affixation, reduplication and compounding /compose. The use of the prefix tend to the use of prefixes me-, ber-, and di-. The use of prefixes me- (n) are also widely used, which is in this prefix there is smelting because the basic word starting with the letter j and c. The use confics also tend to be monotonous to the old spelling because of the dominant use of konfiks ke- + -nya, memper- and -nya, me- and -nya, ke- and -an, me- and -kan, and se- and -nya. The use of reduplication in the Sarinah: Kewadjiban Wanita dalam Perdjoangan Republik Indonesia novel consists of idiomatic reduplication, whole reduplication, passage reduplication, and reduplication affix. The use of compounding/ compositumin several categories that found arecopulatif compound and deternatif compound. Implementation of morphological processes of Indonesian language study in high school related with morphological processes that can be applied is the use of affixation and compounding.